The Withering away of which State? - De Jong, Zachary (Identities: Journal for Politics, Gender and Culture, 2022)
Communism and the state share, historically, an intrinsic link, so much so that, at least in North America, state control, totalitarianism, and communism have become practically synonymous with each other in general parlance. Marx, and countless Marxists after him, however, advocated for the disappearance of the state, taking aim at the state’s role, and complicity in, forwarding and perpetuating class inequalities, and the entire structure of capital itself. In this same sense, the state can be seen as a form of meta-structure, reinforcing through law, force, and ideology, the internal logic of capitalism itself. Thus, while also exploring what the state as such is, this talk will ask: what then does the disappearance of the state mean today, how do these forms of hegemonic control function across a wide range of variegated contexts, and through what modes can we resist them? Author(s): Zachary De Jong Title (English): The Withering away of which State? Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 48-56 Page Count: 8 Citation (English): Zachary De Jong, "The Withering away of which State?,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 48-56. Author Biography Zachary De Jong, Institute of Social Sciences and Humanities, Skopje Zachary De Jong is a researcher and graduate student at the Institute of Social Sciences and Humanities, Skopje. His research is focused on examining Marxist and materialist conceptions of what a post-capitalist or communist society could look like going forward. He has published an article on this topic entitled: “Reimagining the Oikos” (Identities: Journal for Politics, Gender and Culture).